Analysis and simulation of 7-level and 9-level cascaded H-bridge multi-level inverters - Banka, Sujatha; Sunil Kumar, Chava; Salkuti, Surender Reddy; Bhupathiraju, Sai Sruthi; Balakishan, Kasoju Pragathi; Chaturya, Paipoti Pooja; Namineni, Rishitha (International Journal of Applied Power Engineering (IJAPE), 2025)
Multi-level inverters (MLIs) have created a new revolution in high-power and medium-voltage applications in industry and research. In recent years, cascaded multi-level inverters have gained significant interest due to their ability to generate high-quality output waveforms with reduced total harmonic distortion (THD). This paper discusses the analysis and simulation of 7-level and 9-level cascaded H-bridge multi-level inverters using mathematical models and simulation tools. The proposed research puts emphasis on evaluating the performance and control strategies of these inverters. The control strategies, including pulse width modulation (PWM) techniques, are discussed in depth, with a focus on their effect on output waveform quality and reduction of THD. The simulation results are compared to showcase the advantages offered by the cascaded multi-level inverters in terms of waveform quality. The findings demonstrate the superior performance and power quality advantages offered by these multi-level inverters compared to traditional two-level inverters. Additionally, a passive LC filter is designed and implemented along with a multi-level inverter configuration that helps to keep the THD within the limits specified by IEEE standards.